USING STORY CIRCLE TO IMPROVE STUDENTSâ€™ ABILITY IN WRITING NARRATIVE TEXT - Diah Paramita Sari; M. Sabri (INOVISH JOURNAL, 2017)
Abstract: This study aims to discuss one way of solving the problems of students in writing narrative texts, namely by using Story Circle. In this activity, students were divided into several groups and then the teacher read one of the narrative texts in the form of fairy tales, fables or legends that they have never known before. They rewrote the text they had heard before in accordance with the generic structure and language features found in the narrative text, but with different versions according to their imagination. After they wrote the first few sentences of the story on the paper they had each, the students gave the paper to a colleague on their left. Then, their colleagues added the next sentence based on the idea of the story that had been written before. This activity continued until they completed the complication section of the story. When the paper returned to the real owner, the student wrote down the resolution. Activities Story Circle is expected to be one of the variations of learning to write in the class so that students are able to pour their ideas properly and precisely, especially in English. In addition, through this technique, students can creatively and freely develop story ideas.Â Keywords: writing, narrative text, story circleLecturers of State Polytechnic of BengkalisState Polytechnic of BengkalisJl.Bathin Alam-Sungai Alam, Bengkalis-Riau, 28711 Phone: (+6277) 24566,Fax: (+2766) 800 1000